Engagement of Chinese EFL learners in problem-based learning: a thematic analysis - Guo, Qian; Ismail, Lilliati; Jamil, Halimah; Luo, Shujie; Sun, Zhubin (Sciedu Press, 2025)
Academic engagement is crucial for student success, prompting educators to explore various methods to enhance engagement. This study examines the use of Problem-Based Learning (PBL) to enhance engagement among English as a Foreign Language (EFL) undergraduates in China. Employing a qualitative approach, the research incorporates classroom observations and field notes to assess the impact of PBL on learner engagement in EFL contexts. Through thematic analysis, the study finds that PBL significantly enhances engagement across behavioral, emotional, and cognitive dimensions. The results indicate that integrating PBL into EFL instruction could substantially increase student engagement. Recommendations include embedding PBL strategies in EFL courses and developing a PBL instructional model tailored to the specifics of Chinese education. Future research should investigate PBL’s effectiveness with diverse learner populations to further elucidate its impact.